Analisis Respon Peserta Didik Terhadap Penggunaan Model Pembelajaran Game Based Learning Berbasis Wordwall Di SMA Negeri 1 Kabila - Botutihe, Vanessa; Eraku, Sunarty S.; Masruroh, Masruroh (Universitas Negeri Gorontalo, 2025)
This study analyzes students' responses to the use of the Wordwall application-based Game Based Learning model at SMA Negeri 1 Kabila. The purpose of this study is to examine the effectiveness of this learning model in improving student activity, participation, and learning outcomes in geography. This study uses a quantitative approach with a descriptive design, involving 10th grade students as subjects. Student activity data were collected through questionnaires and observations, analyzed descriptively using frequency, percentage, and average. The results showed a significant increase in student engagement from the first to the fourth meeting, from 68.88% to 97.77%. This increase reflects students' positive response to a more interactive and enjoyable learning method compared to conventional methods. The Wordwall-based Game-Based Learning model proved to be effective in increasing student engagement and concentration, which contributed to improved geography learning outcomes. Thus, this model is an innovative and relevant alternative for learning in the digital age and is in line with the Merdeka curriculum requirements at SMA Negeri 1 Kabila. This study also emphasizes the importance of utilizing digital learning media that can stimulate student motivation and interest in the teaching and learning process. The use of Wordwall as a Game-Based Learning platform provides a varied and enjoyable learning atmosphere that facilitates the understanding of abstract geography concepts. In addition, this study highlights the role of teachers as facilitators in integrating technology with learning methods that can maximize student potential. The implications of the research results show that the application of Wordwall-based Game-Based Learning can be used as an effective learning strategy to improve the quality of education in high schools.